Effects of the menstrual cycle on the performance of female football players. A systematic review - Hamed-Hamed, Dina; González-Muñoz, Ana; Cuevas-Cervera, Maria; Perez-Montilla, Jose Javier; Aguilar-Nuñez, Daniel; Aguilar-García, María; Pruimboom, Leo; Navarro-Ledesma, Santiago (Frontiers in Physiology, 2024)
Background: Women's football has been booming for a few years now, which has led to an increase in the expectation of the players' performance, leading to a more detailed study of women's physiology in the field of sports.To analyze the scientific evidence on the influence of menstruation on the performance of female footballers, as well as to analyze the methodological quality of the studies included in this review.The possible hormonal effects of the menstrual cycle phases on the performance of female footballers were analyzed. The databases used to conduct the searches were Pubmed, Scopus, Virtual Health Library, Web of Science, EBSCO and the Cochrane Library. All included studies met the inclusion criteria. The Cochrane risk of bias tool was used. This systematic review protocol was registered at the International Prospective Register of Systematic Reviews (PROSPERO: CRD42023390652).Results: A total of nine clinical trials were included in this review. A low quality of evidence was observed in the studies. Not all the results support the idea that the menstrual cycle phases can alter the performance of female footballers.This systematic review shows that there is a great deal of controversy about the influence of the menstrual cycle phases on the performance of female footballers. Studies are focused on solely biological factors and gender is normally no part of those studies. Further research with larger samples, and taking not only biological but also sociological factors, are necessary to determine the effects of menstruation on the performance of female footballers.